Mechanistic investigations of the Au catalysed C–H bond activations in on-surface synthesis. Issue 23 (31st May 2018) - Niu, Kaifeng; Lin, Haiping; Zhang, Junjie; Zhang, Haiming; Li, Youyong; Li, Qing; Chi, Lifeng
Abstract : The catalytic activities of gold-based catalysts for on-surface C–H bond activation increases as the effective d-band center approaching to the fermi level. Abstract : Recently, Au-based nanostructures have attracted extensive interest due to their excellent activities in heterogeneous catalysis. The reaction mechanisms have been interpreted qualitatively by the quantum confinement effect due to the low-coordination of Au atoms in nanostructures. In this work, systematic first-principles calculations were carried out to obtain an in-depth understanding of the origin of C–H bond activations with Au-based catalysts in on-surface synthesis. Combining density functional theory (DFT) calculations and scanning tunneling microscopy (STM) studies, we reveal that the d-band centre and the d-band width of the Au-5d z 2 orbital in an energy window of −6.80 to 0.00 eV may serve as theoretical descriptors for the prediction of the activity of Au catalysts in C–H bond activations. This work may therefore inspire further investigations on the design of new catalysts.